Fibrocyte measurement in peripheral blood correlates with number of cultured mature fibrocytes in vitro and is a potential biomarker for interstitial lung disease in Rheumatoid Arthritis - Søren Andreas Just; Hanne Lindegaard; Eva Kildall Hejbøl; Jesper Rømhild Davidsen; Niels Bjerring; Søren Werner Karlskov Hansen; Henrik Daa Schrøder; Inger Marie Jensen Hansen; Torben Barington; Christian Nielsen (Respiratory Research, 2017)
Abstract Background Interstitial lung disease (ILD) can be a severe extra-articular disease manifestation in Rheumatoid Arthritis (RA). A potential role of fibrocytes in RA associated ILD (RA-ILD) has not previously been described. We present a modified faster method for measuring circulating fibrocytes, without intracellular staining. The results are compared to the traditional culture method, where the number of monocytes that differentiate into mature fibrocytes in vitro are counted. The results are following compared to disease activity in patients with severe asthma, ILD, RA (without diagnosed ILD) and RA with verified ILD (RA-ILD). Method CD45+ CD34+ CD11b+ (7-AAD− CD3− CD19− CD294−) cells were isolated by cell sorting and stained for pro-collagen type 1. Thirty-nine patients (10 RA, 9 ILD and 10 with severe asthma, 10 with RA-ILD) and 10 healthy controls (HC) were included. Current medication, disease activity, pulmonary function test and radiographic data were collected. Circulating fibrocytes were quantified by flow cytometry. Peripheral blood mononuclear cells were isolated and cultured for 5 days and the numbers of mature fibrocytes were counted. Results 90.2% (mean, SD = 1.5%) of the sorted cells were pro-collagen type 1 positive and thereby fulfilled the criteria for being circulating fibrocytes. The ILD and RA-ILD groups had increased levels of circulating fibrocytes compared to HC (p < 0.05). Levels of circulating fibrocytes correlated overall to number of monocytes that subsequently in vitro differentiated to mature fibrocytes (r = 0.81, p < 0.001). RA patients with pathologically reduced diffusion capacity for carbon monoxide adjusted for hemoglobin (DLCOc) in both the RA and in the combined RA + RA-ILD group, had significantly higher levels of both circulating and number of cultured mature fibrocytes (both p < 0.05). In both groups, the level of circulating fibrocytes and number of mature fibrocytes in culture also correlated to a reduction in DLCOc (r = −0.61 an r = −0.58 both p < 0.05). Conclusions We presented a fast and valid method for measuring circulating fibrocytes using flow cytometry on lysed peripheral blood. Further, we showed for the first time, that the level of circulating fibrocytes correlated with the number of peripheral blood mononuclear cells, that differentiated into mature fibrocytes in vitro. Reduced DLCOc was correlated with high levels of circulating and mature fibrocytes in RA, which have not been reported previously. In such, this study suggests that fibrocytes may exhibit an important role in the pathogenesis of RA-ILD, which requires further clarification in future studies. Trial registration ClinicalTrials.gov : NCT02711657 , registered 13/3–2016, retrospectively registered.